Enhancing Writing Achievement Through a Digital Learning Environment: Case Studies of Three Struggling Adolescent Male Writers. Issue 1 (2nd January 2017) - Pruden, Manning; Kerkhoff, Shea N.; Spires, Hiller A.; Lester, James
ABSTRACT: The aim of this study was to explore how Narrative Theatre, a narrative-centered digital learning environment, supported the writing processes of 3 struggling adolescent male writers. We utilized a multicase study approach to capture 3 sixth-grade participants' experiences with the digital learning environment before, during, and after writing. The case studies provided detailed portraits of the writers as well as insights into their digital writing processes related to student interest, student ability, and value for writing. The across-case analysis revealed 3 themes (i.e., choice, scaffolding, and self-efficacy) that illustrated how the digital learning environment contributed to the students' writing experiences. Future research and development will focus on the addition of text animation for student products and the degree to which this feature further contributes to engagement and proficiency with struggling writers.